Fair value accounting and gains from asset securitizations: A convenient earnings management tool with compensation side-benefits - Dechow, Patricia M.; Myers, Linda A.; Shakespeare, Catherine (Journal of Accounting and Economics, 2010)
Accounting rules for valuing retained interest from securitizations require management to make assumptions concerning discount rates, default rates, and prepayment rates. These assumptions provide management with discretion to determine the “gain on sale” of the receivables. We investigate whether CEO compensation is less sensitive to securitization gains than to other earnings components in the presence of proxies for how independent (outsiders, females, fewer CEO-selected directors) and informed (financial expertise) directors are. Overall, our results do not suggest that better “monitoring” reduces earnings management or CEO pay-sensitivity to reported securitization gains. Our results suggest that CEOs are rewarded for the gains they report and boards do not intervene.